Evaluating the impact of the flipped classroom model on senior secondary students' mathematics achievement: a quasi-experimental study in Nigeria - Asanre, Akorede; Sondlo, Aviwe; Adedeji, Abdullateef (Universitas Terbuka, 2025)
The ongoing poor achievement in mathematics underlines the need for effective instructional approaches that can boost students’ comprehension and performance. The study aimed to examine the effects of the flipped classroom model and gender on the mathematics achievement of senior secondary school students in Ijebu Ode, Ogun State, Nigeria. Fifty-four students were divided into an experimental group, which received flipped classroom instruction, and a control group, which was taught through traditional methods. Data were collected over six weeks using the Mathematics Achievement Test (MAT) with a reliability coefficient of 0.74, along with pre- and post-test assessments. The data were analyzed using ANCOVA. ANCOVA results revealed that the flipped classroom model had a statistically significant effect on students' mathematics achievement (p < 0.05), confirming the model's impact on academic achievement. The gender analysis showed that both male and female students benefited equally from the flipped classroom model, highlighting its inclusivity as an effective teaching strategy. The study concludes that the flipped classroom model significantly improves mathematics achievement in Ogun State’s secondary schools. It recommends adopting this model, coupled with appropriate teacher training and resource allocation, to promote equitable and enhanced learning outcomes.